Phase 1 study combining elotuzumab with autologous stem cell transplant and lenalidomide for multiple myeloma - Seunghee Kim-Schulze; Sundar Jagannath; Sacha Gnjatic; Ajai Chari; Samir Parekh; Keren Osman; Selma Bekri; Hearn Jay Cho; David G Coffey; Adolfo Aleman; Simone Kats; Amishi Dhadwal; et al. (Journal for ImmunoTherapy of Cancer)
Background Autologous stem cell transplantation (ASCT) after induction therapy improves disease-free survival for patients with multiple myeloma (MM). While the goal of ASCT is to render a minimal disease state, it is also associated with eradication of immunosuppressive cells, and we hypothesize that early introduction of immunotherapy post-ASCT may provide a window of opportunity to boost treatment efficacy.Methods We conducted a phase 1 clinical trial to investigate the application of autologous lymphocyte infusion and anti-SLAMF7 monoclonal antibody, elotuzumab, after ASCT in patients with newly diagnosed MM previously treated with induction therapy. In addition to CD34+ stem cells, peripheral blood mononuclear cells were harvested prior to transplant and infused on day 3 after stem cell infusion to accelerate immune reconstitution and provide autologous natural killer (NK) cells that are essential to the mechanism of elotuzumab. Elotuzumab was administered starting on day 4 and then every 28 days after until 1 year post-ASCT. Cycles 4–12 were administered with standard-of-care lenalidomide maintenance.Results All subjects were evaluated for safety, and 13 of 15 subjects completed the treatment protocol. At 1 year post-ASCT, the disease status of enrolled subjects was as follows: five stringent complete responses, one complete response, six very good partial responses, one partial response, and two progressive diseases. The treatment plan was well tolerated, with most grade 3 and 4 AEs being expected hematologic toxicities associated with ASCT. Correlative analysis of the immune microenvironment demonstrated a trend toward reduced regulatory T cells during the first 3 months post-transplant followed by an increase in NK cells and monocytes in patients achieving a complete remission.Conclusions This phase 1 clinical trial demonstrates that early introduction of immunotherapy after ASCT is well tolerated and shows promising disease control in patients with MM, accompanied by favorable changes in the immune microenvironment.Trial registration number NCT02655458.